PERANCANGAN STUDENT SERVICE CENTER MELALUI SISTEM KIOS INFORMASI SMAK PENABUR HARAPAN INDAH BEKASI - Sarimolle, Francis M.; Saragih, Hoga (Teknik dan Ilmu Komputer, 2013)
This paper is aimed at answering the needs of SMAK Penabur Harapan Indah students to get information from the Student Service Center using Information Kiosk System concept. There is a tendency that students need up-to-date information to support their school work. This system will help improving the information service quality to meet the studentsâ need for more accurate information. The service will be an added value for SMAK Penabur Harapan Indah âBekasi in competing with other schools in Bekasi area. SDLC used in this paper is the Water Fall type. It is expected that Student Service Centre designed for SMAK Penabur Harapan Indah can be the solution to the information problem, especially information for the students.Â Keywords: information, information system, information kiosk, student service center, student requirementsÂ